REGIONAL ORDER AND TRANSFORMATION OF WATER REGIME IN CONTEMPORARY INNER ASIA - A. V. Mikhalev (Сравнительная политика)
This paper is a study of water-sharing disputes in Inner Asia. The focal point is the issue of fresh water-sharing in the conditions of regional post-Soviet political order. The article is an attempt to verify a hypothesis: is there a correlation between hydro power control system and regional polticial order? We study the relations between Russia, China, and Mongolia that deal with transboundary rivers which fl ow into Lake Baikal. This lake is the world’s biggest fresh-water lake and is under protection by the UNESCO. The proposed paper is centered around the idea that institutional conditions influence the legitimization of rights on hydro reserves. The research is based on the methods of neo-institutionalism which is used to study the regional political order. The empirical basis of the paper is made up of legal acts on the distrubution of transboundary waters, speeches of Russian and Mongolian statesmen, offi cial statistical data, ecological monitoring data, and regional mass-media data. Our basic conclusion: the processes undergoing in Inner Asia could lead to a new political order in the foreseeable future. The ideas, values, and infrastructural macro-projects can change both the balance of power in the region and the level of water consumption. The arising ecological problems therefore become politicized.